Penetrance of Breast Cancer Susceptibility Genes From the eMERGE III Network. Issue 4 (8th May 2021) - Fan, Xiao; Wynn, Julia; Shang, Ning; Liu, Cong; Fedotov, Alexander; Hallquist, Miranda L G; Buchanan, Adam H; Williams, Marc S; Smith, Maureen E; Hoell, Christin; Rasmussen-Torvik, Laura J; Peterson, Josh F; et al.
Abstract: Background: Unbiased estimates of penetrance are challenging but critically important to make informed choices about strategies for risk management through increased surveillance and risk-reducing interventions. Methods: We studied the penetrance and clinical outcomes of 7 breast cancer susceptibility genes ( BRCA1, BRCA2, TP53, CHEK2, ATM, PALB2, and PTEN ) in almost 13 458 participants unselected for personal or family history of breast cancer. We identified 242 female participants with pathogenic or likely pathogenic variants in 1 of the 7 genes for penetrance analyses, and 147 women did not previously know their genetic results. Results: Out of the 147 women, 32 women were diagnosed with breast cancer at an average age of 52.8 years. Estimated penetrance by age 60 years ranged from 17.8% to 43.8%, depending on the gene. In clinical-impact analysis, 42.3% (95% confidence interval = 31.3% to 53.3%) of women had taken actions related to their genetic results, and 2 new breast cancer cases were identified within the first 12 months after genetic results disclosure. Conclusions: Our study provides population-based penetrance estimates for the understudied genes CHEK2, ATM, and PALB2 and highlights the importance of using unselected populations for penetrance studies. It also demonstrates the potential clinical impact of genetic testing to improve health care through early diagnosis and preventative screening.